2014
DOI: 10.3324/haematol.2013.103085
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of pan-KIR2D blockade with IPH2101 in smoldering multiple myeloma

Abstract: LETTERS TO THE EDITOR © F e r r a t a S t o r t i F o u n d a t i o n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 14 publications
1
81
0
Order By: Relevance
“…Although no objective responses were seen, IPH2101 is safe and tolerable at doses that achieve full inhibitory KIR saturation [66]. The following Phase II clinical trial was recently completed in SMM patients where immune cells are still intact [65]. Encouragingly, results from this trial showed that NK cells elicit a tumor specific cytotoxic response, without harming normal cells [65].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…Although no objective responses were seen, IPH2101 is safe and tolerable at doses that achieve full inhibitory KIR saturation [66]. The following Phase II clinical trial was recently completed in SMM patients where immune cells are still intact [65]. Encouragingly, results from this trial showed that NK cells elicit a tumor specific cytotoxic response, without harming normal cells [65].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…The following Phase II clinical trial was recently completed in SMM patients where immune cells are still intact [65]. Encouragingly, results from this trial showed that NK cells elicit a tumor specific cytotoxic response, without harming normal cells [65]. This early clinical activity suggests that a more efficacious treatment strategy of manipulating the immune system with blockers of inhibitory NK cell function might improve anti-MM responses induced by anti-BCMA mAbs.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, treatment of mice bearing the lenalidomide-resistant RMA T-cell lymphoma with this combination led to in vivo tumor elimination [102]. Recently, the results of a phase I and a phase II clinical trial with IPH2101 have been reported in patients with relapsed/refractory or smoldering MM, respectively [103,104]. Although deemed safe, the phase II clinical trial showed no clinical response to IPH2101 alone.…”
Section: Adoptive Nk-cell Transfermentioning
confidence: 99%
“…Novel tumor immunotherapies have been developed that block the inhibitory killer immunoglobinlike receptors (KIRs) on human NK cells that are functionally homologous to murine Ly49s (4). However, clinical trials of anti-KIR checkpoint blockade failed to show efficacy in treating patients with smoldering multiple myeloma (5). A better understanding of the in vivo functions of inhibitory NK-cell receptors is important for improving checkpoint blockade of NK cells.…”
mentioning
confidence: 99%